Defining postnatal growth failure among preterm infants in Indonesia - Rohsiswatmo, Rinawati; Kaban, Risma Kerina; Sjahrulla, Muhamad Azharry Rully; Hikmahrachim, Hardya Gustada; Marsubrin, Putri Maharani Tristanita; Roeslani, Rosalina Dewi; Iskandar, Adhi Teguh Perma; Sukarja, Distyayu; Kautsar, Ahmad; Urwah, Ivo (Frontiers in Nutrition, 2023)
Background: Postnatal growth failure (PGF) frequently occurred among preterm infants with malnutrition. Decline in weight-for-age z-score 1.2 has been proposed to define PGF. It was unknown whether this indicator would be useful among Indonesian preterm infants. Methods: Infants <37 weeks of gestational age born between 2020-2021, both stable and unstable, were recruited into a prospective cohort study during hospitalization in level III neonatal intensive care unit at the Cipto Mangunkusumo General Hospital, Jakarta, Indonesia. The PGF prevalence as defined by the weight-for-age z-score <-1.28 (<10th percentile) at discharge, weight-for-age z-score <-1.5 (<7th percentile) at discharge, or decline in weight-for-age z-score 1.2 from birth till discharge were compared. Association between those PGF indicators with preterm subcategory and weight gain was assessed. Association between the decline in weight-for-age z score 1.2 with duration to achieve full oral feeding and time spent for total parenteral nutrition were analyzed. Results: Data were collected from 650 preterm infants who survived and discharged from the hospital. The weight-for-age z-score <-1.28 or <-1.5 defined 307 (47.2%) and 270 (41.5%) subjects with PGF, respectively. However, both indicators did not identify any issue of weight gain among subjects with PGF, questioning their reliability in identifying malnourished preterm infants. In contrast, the decline in weight-for-age z-score 1.2 only defined 51 (7.8%) subjects with PGF, in which this indicator revealed that subjects with PGF had an issue of weight gain. Next, history of invasive ventilation was identified as a risk factor of preterm infants to contract from PGF. Finally, the decline in weight-for-age z-score ≥1.2 confirmed that preterm infants with PGF had longer time to be fully oral fed and longer duration for total parenteral nutrition than the ones without PGF. Conclusion: The decline in weight-for-age z-score ≥1.2 was useful to identify preterm infants with PGF within our cohort. This could reassure pediatricians in Indonesia to use this new indicator.